ASSESSMENT OF THE DISPLAY QUALITY (FEATURES) OF THE BATU WHITE VILLAGE WEBSITE, SECOTONG DISTRICT, WEST LOMBOK - Basuki Srihermanto; Siti Yulianah; Ramdani Abd. Hafizh (Bajang Institute, 2024)
Republic of Indonesia Law no. 6/2016 concerning villages states that Regional Governments are obliged to develop village information systems in carrying out e-government towards good governance. Currently, the number of e-government in Indonesia continues to increase, but in terms of quality there are still many that do not meet the quality standards of a Village Website. In fact, the appearance of the Village Website has a very big influence on the success of e-government. The Batu Putih Village website has represented Batu Putih village as a source of village information to the world. However, the quality of the Batu Putih Village website is still far from expectations, research observations show that the Batu Putih Village website still needs a lot of improvement. The website features are not yet functioning optimally and the information available is no longer up to date. Research using the Qualitative Description method provides input to the management of the Batu Putih Village Website so that maintenance can be carried out on the Batu Putih Village website so that it can become a higher quality Village website so that it can display more valid and accurate Village information